2006
DOI: 10.1111/j.1399-302x.2006.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of DNA adenine methyltransferase alters virulence factors in Actinobacillus actinomycetemcomitans

Abstract: DNA adenine methyltransferase (DAM) plays critical roles in diverse biological pathways in gram-negative bacteria, and specifically in regulating the expression of virulence genes in several organisms. Actinobacillus actinomycetemcomitans plays an important role in the pathogenesis of juvenile and adult periodontal disease, yet little is known about its mechanisms of gene regulation. DAM is shown here to directly or indirectly affect well-known A. actinomycetemcomitans virulence factors. A mutant A. actinomyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Furthermore, A. actinomycetemcomitans dam mutants show reduced invasion of epithelial cells (Wu et al , 2006). …”
Section: Roles Of Dna Adenine Methylation In Host-pathogen Interactionsmentioning
confidence: 99%
“…Furthermore, A. actinomycetemcomitans dam mutants show reduced invasion of epithelial cells (Wu et al , 2006). …”
Section: Roles Of Dna Adenine Methylation In Host-pathogen Interactionsmentioning
confidence: 99%
“…19 The present study indicated that the DAM-deficient strain VT 1560 showed the reduced capacity to induce hBD-2 and IL-8 by trend compared to the native strain, which may be related to a reduction in virulence of this mutant. Wu et al 19 discussed that the observed invasion deficiency was based on an adhesion deficiency rather than on a change in the ability to invade, which is in accordance to the present observations that could be a result of reduced interactions between biofilms and epithelial cells.…”
Section: Discussionmentioning
confidence: 56%
“…Single-species biofilms were grown in a stationary biofilm forming system modified from Guggenheim et al 28 The following strains of A. actinomycetemcomitans were investigated: Y4 (ATCC 43718), VT 1169 a derivate of SUNY 465 and VT 1560 the DAM knockout strain cloned from VT 1169. 19 The parent strain (VT1169) is a spontaneous rifampinnalidixic acid resistant derivate of a smooth-phenotype A. actinomycetemcomitans strain (SUNY 465). 30 The strain ATCC 43718 is a spontaneous smooth-colony variant of the respective clinical strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA adenine methyltransferase (DAM) has been identified in oral bacteria and represents an important role in the control of the expression of virulent genes. Wu et al [42] reported that DAM-mediated methylation may regulate genes required for the invasion process of A. actinomycetemcomitans.…”
Section: Factors That Modify Epigenetic Mechanisms and Periodontal DImentioning
confidence: 99%